Association between carotid stenosis or lacunar infarction and incident dementia in patients with vascular risk factors. (27th August 2014) - Kitagawa, K.; Miwa, K.; Yagita, Y.; Okazaki, S.; Sakaguchi, M.; Mochizuki, H.
<x xml:space="preserve">Abstract</x> Background and purpose The association between vascular risk factors and dementia is of interest. Several studies have shown that cerebral small vessel disease (SVD) is associated with dementia. However, the association between cerebral large vessel disease (LVD) and dementia has not been thoroughly examined. Methods The Osaka Follow‐up Study for Carotid Atherosclerosis, Part 2, was a prospective cohort study of cardiovascular events and dementia in which patients (n = 1106) with vascular risk factors underwent carotid ultrasound. Of these patients, 600 who had normal cognitive function were included and underwent brain magnetic resonance imaging. The presence of lacunar infarction and carotid stenosis served as markers for SVD and LVD, respectively. Results Amongst 600 patients (mean 68 years, 57% men), 261 (44%) showed lacunar infarction and 94 (16%) showed carotid stenosis. During the follow‐up period (median 8.0 years), 57 patients had incident dementia. Patients with carotid stenosis and lacunar infarction were significantly more likely to be diagnosed with dementia (log‐rank test, P = 0.037 and P < 0.001, respectively). The association between lacunar infarction and dementia remained significant after adjusting for risk factors including stroke history, apolipoprotein E genotype and years of education (hazard ratio 2.64, 95% confidence interval 1.22–6.09). However, the presence of carotid stenosis was not associated with incident dementia after adjusting for age and sex (P = 0.477). Conclusions This study demonstrated that carotid stenosis had little association with dementia, but lacunar infarction had a significant association. The impact of SVD on dementia could be much greater than that of LVD.